Infrastructures of abstraction: how computer science education produces anti-political subjects - Malazita, James W.; Resetar, Korryn (Digital creativity (Exeter), 2019)
Abstraction, defined in Computer Science (CS) as bracketing unnecessary information from diverse components within a system, serves as a central epistemological axis in CS disciplinary and pedagogical practices. Its impressions can be seen across curricula, syllabi, classroom structures, IT systems; and other dimensions of the epistemic infrastructure of CS (Malazita [Forthcoming]. "Epistemic Infrastructures, the Instrumental Turn, and the Digital Humanities." In Debates in the Digital Humanities: Infrastructures, Institutions at the Interstices, edited by Angel Nieves, Siobhan Senier, and Anne McGrail. University of Minnesota Press). As we will argue in this essay, abstraction in CS serves as an epistemic, cultural, and ideological wall to integrated critical-technical education, rather than as a bridge. Further, this wall is disguised as a bridge: the common language used across CS and the Humanities gives the impression that abstraction can be leveraged as a boundary object (Star [2010]. "This is Not a Boundary Object: Reflections on the Origin of a Concept." Science, Technology, & Human Values 35 (5): 601-617), as a point of connection among conflicting or incommensurable epistemic cultures (Knorr Cetina [1999]. Epistemic Cultures: How the Sciences Make Knowledge. Cambridge: MIT Press). Rather, computational knowledge practices leverage abstraction's homographic-ness, epistemically structuring collaborative efforts in anti-political ways. To illustrate the impacts of abstraction, this essay will introduce 'Critical CS1,' a hybrid pedagogical approach to teaching Computer Science through feminist and critical race theory. However, other components of the epistemic infrastructures of Computer Science, from curricular structure, to IT systems, to classroom culture, to the epistemic practices of coding itself, resisted these intervention efforts, and reproduced marginalizing effects upon students within the course.